(untitled) (The Pakistan Development Review, 2015)
The objective of this paper is to investigate the incidence of different types of shocks in rural Pakistan and identify the household characteristics that are associated with this phenomenon. It is observed that one-third of households experience an adverse shock, be it natural/agricultural, economic, social or relating to health. The natural/agricultural shocks have major share in the total burden of shocks while the households‘ coping mechanism is overwhelmingly informal and largely asset-based. The poorest of the households adopt behaviour-based strategies like reducing food consumption, employ child labour, work more hours etc. Overall, households of with less educated heads, high dependency ratio, large household size, low welfare ratio, farm household, ownership of land and residing in south Punjab or Sindh are more vulnerable to suffer shocks, particularly of income. Vulnerability in terms of a decline in consumption is observed for households who are hit by natural/agricultural or health shocks. For all these reasons, a gradual shift from traditional emergency relief measures towards ex-ante actions to reduce and mitigate hazard impacts should be encouraged along with non- exploitative credit and more effective safety nets. JEL Classification: C21, C25, I32 Keywords: Shocks, Vulnerability, Poverty